Effects of the Marinating Process on the Quality of the Domesticated Reindeer (Rangifer Tarandus) By-products - Benzik, Ilya; Brazhnaia, Inna; Bogdan, Elena; Ershov, Alexander (KnE Life Sciences, 2020)
The development of methods for the complete and complex processing of raw food materials is one of the main ways to achieve the efficiency of its use: reduce production costs, expand products range and increase products demand. Over the last years, growing attention is paid to the search and development of new technologies of the processing of non-traditional and underutilized types of food materials, such as meat and by-products from alternative animal species. The research was aimed at studying the influence of the marinating process on the quality of the newly developed food product. The object of research was the tongue of domesticated reindeer, the underutilized raw materials of the Kola Peninsula. Product samples were taken in 2012-2016 on the basis of the agricultural production cooperative ”Tundra”, research was carried out on the basis of the Department of Food Production Technologies of the Federal State Budgetary Educational Institution of Higher Education ”Murmansk State Technical University”. The effects of marinating and duration of heat treatment on the quality of the product samples was studied. The parameters characterizing the generalized indicator of quality were selected - organoleptic (appearance, flavor and taste), physical (cutting force) and microbiological. The optimal composition of the marinade is proposed. The technology of culinary processing of the domesticated reindeer tongue was optimized.